Capillostrongyloides morae sp. n. (Nematoda: Capillariidae) from deep-sea fish (Teleostei, Moridae) in the western Mediterranean Sea - González-Solís, David; Carrassón, Maite; Pérez-del-Olmo, Ana (Folia parasitologica, 2014)
A new capillariid nematode, Capillostrongyloides morae sp. n., is described from specimens collected from the stomach and intestine of the common mora, Mora moro (Risso), and the Mediterranean codling, Lepidion lepidion (Risso) (both Gadiformes, Moridae), off the Mediterranean coasts of Spain. The new species shows similar morphological features as other congeneric species occurring in freshwater and marine fishes, but it differs in the length of the body and spicules, the size of the caudal bursa, and the presence of an elevated anterior vulvar lip. Capillostrongyloides morae sp. n. is the second species within the genus for which the presence of a stylet is reported, and the first one in which this structure along with the distribution of cephalic papillae and oral structures (e.g. lips and lobes) are clearly shown by using scanning electron microscopy.
Keywords: Female; Nematoda; nemoci ryb; hlístice; Fishes; Animals; Středozemní moře; Mediterranean Sea; ženské pohlaví; Fish Diseases; mužské pohlaví; Male; Nematode Infections; zvířata; ryby; nematodózy